1997
DOI: 10.1073/pnas.94.18.9674
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome positioning and directionality of cell movements

Abstract: In several cell types, an intriguing correlation exists between the position of the centrosome and the direction of cell movement: the centrosome is located behind the leading edge, suggesting that it serves as a steering device for directional movement. A logical extension of this suggestion is that a change in the direction of cell movement is preceded by a reorientation, or shift, of the centrosome in the intended direction of movement. We have used a fusion protein of green f luorescent protein (GFP) and ␥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(100 citation statements)
references
References 41 publications
(33 reference statements)
6
94
0
Order By: Relevance
“…One of the early events that occurs during directed cell migration is the reorientation of the centrosome (26). This is preceded by the extension of a new pseudopod in the migrating cell in the intended direction of movement (26). Centrosome reorientation toward the leading edge has been described in migrating endothelial cells and other cell types (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the early events that occurs during directed cell migration is the reorientation of the centrosome (26). This is preceded by the extension of a new pseudopod in the migrating cell in the intended direction of movement (26). Centrosome reorientation toward the leading edge has been described in migrating endothelial cells and other cell types (27).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that stathmin inhibition interferes with the process of cell migration (23)(24)(25). One of the early events that occurs during directed cell migration is the reorientation of the centrosome (26). This is preceded by the extension of a new pseudopod in the migrating cell in the intended direction of movement (26).…”
Section: Discussionmentioning
confidence: 99%
“…The OSM-stimulated and PKA-dependent reorganization of polarized membrane trafficking from SAC coincides with a stimulated recruitment of PKA to the centrosomal region (van der Wouden et al, 2002). The SAC and other organelles involved in polarized sorting, e.g., the Golgi apparatus, are typically concentrated in the centrosomal region (HobdyHenderson et al, 2003;Rios and Bornens, 2003), and both the centrosome and associated organelles typically face specialized cell surface domains, e.g., the leading lamella in migrating fibroblasts (Ueda et al, 1997) and the apical PM domain in epithelial cells (Buendia et al, 1990). Moreover, in differentiated G 1 cells, one of the centrosomes moves to the apical surface to form the basal body of the primary cilium, a highly specialized membrane domain that extends from the apical surface.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that positioning of the centrosome may determine the direction of cell movement, most probably through the microtubule system. 29,33 Overexpression of Cdc14B has been previously described to result in microtubules bundling and stabilization as well as decreased microtubule nucleation from the centrosome. 22 Thus, it is possible that some of the effects in cell movements may be due to a direct role of Cdc14B on microtubule dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the centrosome is polarized in migrating cells and determines the direction of the movement. 29 We therefore fixed the cells at different time points after wound healing and stained them for γ-tubulin, a centrosomal marker. While the majority of the control cells (62.5%) showed a correct centrosome orientation (that means towards the center of the wound), only a minor part of Cdc14B overexpressing fibroblasts (31.7%) showed proper orientation (Fig.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%